EFFECT OF SPACING AND NITROGEN ON FLORAL AND VASE LIFE PARAMETER OF GLADIOLUS (GLADIOLUS GRANDIFLORUS US GRANDIFLORUS L.) CV. AMERICAN BEAUTY - B. V. THUMAR, A. L. REGAR,; S. L. CHAWLA, L. N. MAHAWER (The Bioscan, 2016)
An experiment conducted on effect of spacing and nitrogen on floral and vase life parameter of gladiolus (Gladiolus grandiflorus L.) cv. American Beauty. The treatments comprised of three levels of spacing (40 x 15 cm, 40 x 20 cm and 40 x 25 cm) and four levels of nitrogen (150, 200, 250 and 300 kg ha-1) in a randomized block design with factorial concept and replicated thrice. The results revealed that wider spacing 40 x 25 cm and fertilized with 250 kg N ha-1 recorded best spike quality and maximum post- harvest life of gladiolus spike characters viz., number of florets per spike, spike fresh weight (g), floret diameter (cm), rachis length (cm), flowering span (days), in-situ spike longevity (days) and vase life (days)